Recalibration of limits to growth: An update of the World3 model - Nebel, Arjuna; Kling, Alexander; Willamowski, Ruben; Schell, Tim (Journal of Industrial Ecology)
Abstract After 50 years, there is still an ongoing debate about the Limits to Growth (LtG) study. This paper recalibrates the 2005 World3‐03 model. The input parameters are changed to better match empirical data on world development. An iterative method is used to compute and optimize different parameter sets. This improved parameter set results in a World3 simulation that shows the same overshoot and collapse mode in the coming decade as the original business as usual scenario of the LtG standard run. The main effect of the recalibration update is to raise the peaks of most variables and move them a few years into the future. The parameters with the largest relative changes are those related to industrial capital lifetime, pollution transmission delay, and urban‐industrial land development time.
Keywords: General Social Sciences; General Environmental Science

Will do? Causes and volitions - Wells, Aaron (Metascience)
Keywords: History and Philosophy of Science; General Social Sciences; History

On the Multimodal Resolution of a Search Sequence in Virtual Reality - Klowait, Nils (Human Behavior and Emerging Technologies)
In virtual reality (VR), participants may not always have hands, bodies, eyes, or even voices—using VR helmets and two controllers, participants control an avatar through virtual worlds that do not necessarily obey familiar laws of physics; moreover, the avatar’s bodily characteristics may not neatly match our bodies in the physical world. Despite these limitations and specificities, humans get things done through collaboration and the creative use of the environment. While multiuser interactive VR is attracting greater numbers of participants, there are currently few attempts to analyze the in situ interaction systematically. This paper proposes a video-analytic detail-oriented methodological framework for studying virtual reality interaction. Using multimodal conversation analysis, the paper investigates a nonverbal, embodied, two-person interaction: two players in a survival game strive to gesturally resolve a misunderstanding regarding an in-game mechanic—however, both of their microphones are turned off for the duration of play. The players’ inability to resort to complex language to resolve this issue results in a dense sequence of back-and-forth activity involving gestures, object manipulation, gaze, and body work. Most crucially, timing and modified repetitions of previously produced actions turn out to be the key to overcome both technical and communicative challenges. The paper analyzes these action sequences, demonstrates how they generate intended outcomes, and proposes a vocabulary to speak about these types of interaction more generally. The findings demonstrate the viability of multimodal analysis of VR interaction, shed light on unique challenges of analyzing interaction in virtual reality, and generate broader methodological insights about the study of nonverbal action.
Keywords: Human-Computer Interaction; General Social Sciences; Social Psychology; Virtual Reality : Multimodality; Nonverbal Interaction; Search Sequence; Gesture; Co-Operative Action; Goodwin; Ethnomethodology

Anonymity and Self-Expression in Online Rating Systems - An Experimental Analysis - Hoyer, Britta; van Straaten, Dirk (Journal of Behavioral and Experimental Economics)
Keywords: General Social Sciences; Economics and Econometrics; Applied Psychology

Rekonstruktive Evaluationsforschung im Kontext praxeologischer Kompetenzdiskurse. Kritische Reflexionen und konzeptionelle Überlegungen zur Dokumentarischen Evaluationsforschung - Bloh, Thiemo (Zeitschrift für Evaluation)
Praxeologische Kompetenzansätze verstehen Kompetenz als sozial erlernt und folglich als relativ zum sozialen Kontext. Damit einher geht die Frage, wie solche praxeologisch gerahmten Kompetenzen eigentlich unabhängig von der sie hervorbringenden Praxis evaluiert werden können – und eben dadurch erst für einen breiteren Kompetenzdiskurs fruchtbar sind. Die Dokumentarische Evaluationsforschung bietet hierzu erste Anhaltspunkte, offenbart aber auch Grenzen, die mit dem Evaluationsverständnis zusammenhängen, sich jedoch in der Forschungspraxis so nicht finden lassen. Aus der Differenz zwischen Methode und Praxis dokumentarischer Evaluation lässt sich formulieren, wie eine praxeologische Evaluation gestaltet werden könnte. Dabei spielt die Formulierung von Referenzrahmen eine zentrale Rolle, welche einerseits der zu evaluierenden Praktik external sein, andererseits praktisch formuliert werden müssen, damit sie soziale Praktiken jenseits ihrer eigenen Sinnhaftigkeit evaluativ (er-)fassen können.
Keywords: Strategy and Management; Applied Psychology; Social Sciences (miscellaneous); Education; Communication; Statistics and Probability

Assistant nurses and orientation to care robot use in three European countries - Tuisku, Outi; Johansson-Pajala, Rose-Marie; Hoppe, Julia Amelie; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten; Gustafsson, Christine; Melkas, Helinä (Behaviour & Information Technology)
Keywords: Human-Computer Interaction; General Social Sciences; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Validation of the student version of the Perceptions of Inclusion Questionnaire in primary and secondary education settings - Knickenberg, Margarita; Zurbriggen, Carmen L. A.; Schwab, Susanne (SAGE Open)
Considering students’ voices and perspectives is indispensable in educational contexts. Therefore, instruments of measurement that are reliable and valid and can be used easily without complications are needed in schools. The Perceptions of Inclusion Questionnaire (PIQ) is a short instrument used to assess three central dimensions of inclusion, namely emotional and social inclusion and academic self-concept. Previous evaluations indicate in general high psychometric properties. This study aimed to evaluate the construct validity of the three scales of the PIQ’s student version using different approaches in two samples from primary (grade 4, N = 721) and secondary (grade 7, N = 393) schools. The results of confirmatory factorial analyses confirmed the PIQ’s three factors in both samples which are also measurement equivalent across grades. Plausible correlations with additional divergent and convergent scales reveal that the PIQ measures the theoretically assumed constructs—emotional and social inclusion as well as academic self-concept—validly.
Keywords: General Social Sciences; General Arts and Humanities

Citizen Social Science in Germany—cooperation beyond invited and uninvited participation - Göbel, Claudia; Mauermeister, Sylvi; Henke, Justus (Humanities and Social Sciences Communications)
Abstract This article presents an overview of characteristics of Citizen Social Science (CSS) in Germany. CSS is defined as scientific research in the humanities and social sciences, carried out in cooperation between professional and non-professional researchers. The study draws on an online survey and semi-structured interviews with project coordinators and co-researchers. It finds that participatory research activities in the humanities and social sciences are very diverse in their disciplinary traditions and organisational settings. Key features of CSS activities initiated inside as well as outside academic institutions are analysed to understand patterns of participation and cooperation. The results show that CSS activities are frequently realised in heterogeneous consortia of academic and non-academic partners. These consortia influence interactions between professional and non-professional researchers. To investigate these observations further, the article extends the analytical gaze from participation of individual volunteers to various forms of cooperation in consortia. This shift in attention brings to sight additional actors and activities that are usually not, or only marginally, considered in discussions about C(S)S. Staff of civil society organisations, municipalities, schools or cross-sectoral initiatives as well as university students are involved in making CSS work. In addition to research tasks, CSS rests on science communication, project management and intermediation activities. This extended perspective captures more diverse constellations of knowledge production in participatory research in the social sciences and humanities than the common focus on participation. In this way, the article aims to lay the groundwork for understanding the functioning of CSS beyond aspects described by the concept of invited and uninvited participation. It shows that CSS activities are not limited to capacitating lay people for participation in science. A more adequate description is that such projects are concerned with facilitating cooperation with co-researchers and other partners in consortia inside and outside of academia. On this basis, the article introduces the notion of cooperation capacity as a heuristic device to propose new prompts for research on CSS as well as for supporting CSS practice.
Keywords: General Economics; Econometrics and Finance; General Psychology; General Social Sciences; General Arts and Humanities; General Business; Management and Accounting

Von lebenden Systemen und gefühlten Zahlen. Eine körpersoziologische Analyse des finanzaufsichtlichen Risikobewertungsregimes - Knoll, Lisa (Österreichische Zeitschrift für Soziologie)
Der hier vorliegende Beitrag erarbeitet Verbindungslinien zwischen Wirtschaftssoziologie (insb. Finanzsoziologie), Soziologie der Bewertung und Körpersoziologie anhand des Falls finanzmarktregulatorischer Risikobewertung. Dabei spielt der analytische Begriff der Prothese (Michel Callon) eine wichtige Rolle. Nach der Finanzkrise kommt es zu einer Neuverteilung von sensorischen Bewertungskompetenzen in einer hierarchisch aufgebauten, vernetzten Wissensarchitektur. Es ist nun die Maschine, der Lebendigkeit attestiert wird, während der Mensch parzellierte Funktionen in einer Apparatur übernimmt. Gleichzeitig soll der Mensch so zu einem adäquaten und beweglichen (spielerischen) Umgang mit Risiken angeregt werden, die man ihm/ihr in einem eher groben und einfachen Aufsichtssystem nicht mehr zutraute (hier wurden „regulatory arbitrage“ und „kreative Buchführung“ zum Problem). Der Aufsatz rekonstruiert die praktischen Orientierungen und kollektiven Erfahrungen dieses finanzaufsichtlichen Umbaus anhand zweier problemzentrierter Interviews. Unter Rekurs auf die Körperbezüge in diesen Interviews wird die Paradoxie eines Systems herausgearbeitet, das nach wie vor auf individuelle Entscheidungsrationalität und -agilität setzt, diese nun aber maschinell zu erschaffen sucht.
Keywords: General Social Sciences

Assistant nurses and orientation to care robot use in three European countries - Tuisku, Outi; Johansson-Pajala, Rose-Marie; Hoppe, Julia Amelie; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten; Gustafsson, Christine; Melkas, Helinä (Behaviour & Information Technology)
Keywords: Human-Computer Interaction; General Social Sciences; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Which “motionese” parameters change with children's age? Disentangling attention-getting from action-structuring modifications - Rohlfing, Katharina; Vollmer, Anna-Lisa; Fritsch, Jannik; Wrede, Britta (Frontiers in Communication)
Modified action demonstration—dubbed motionese— has been proposed as a way to help children recognize the structure and meaning of actions. However, until now, it has been investigated only in young infants. This brief research report presents findings from a cross-sectional study of parental action demonstrations to three groups of 8–11, 12–23, and 24–30-month-old children that applied seven motionese parameters; a second study investigated the youngest group of participants longitudinally to corroborate the cross-sectional results. Results of both studies suggested that four motionese parameters (Motion Pauses, Pace, Velocity, Acceleration) seem to structure the action by organizing it in motion pauses. Whereas these parameters persist over different ages, three other parameters (Demonstration Length, Roundness, and Range) occur predominantly in the younger group and seem to serve to organize infants' attention on the basis of movement. Results are discussed in terms of facilitative vs. pedagogical learning.
Keywords: Social Sciences (miscellaneous); Communication

Editorial: Netzwerke und Vernetzung im Sport - Meier, Heiko; Kukuk, Marc; Riedl, Lars (Sport und Gesellschaft)
Keywords: Philosophy; Social Sciences (miscellaneous); History

Bourdieu and the Quest for Intercultural Transformations - Pöllmann, Andreas (SAGE Open)
Building and expanding on Bourdieu’s notions of cultural capital, habitus, and field, this conceptual article aims to contribute to a better understanding of intercultural transformations. Distancing itself from essentialist reductionism in the analysis of cultures, it associates intercultural transformations with habitus crises through “culture shock,” with the realization of intercultural capital, and with changes in the scope and configuration of cultural pluriformity. In going beyond Bourdieu without abandoning him along the way, the approach outlined in the course of this article combines a range of conceptual tools which may prove to be useful in sustaining struggles for social justice in educational institutions and in society at large.
Keywords: General Social Sciences; General Arts and Humanities

Intergenerational Value Similarity and Subjective Well-Being - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on the association of intergenerational value similarity and adult children’s and parents’ subjective well-being, on the linkage between relationship quality and subjective well-being. Mediation effects of the relationship quality on the associations between value similarity and subjective well-being were focused. The sample consisted of 600 adult German children (53.8% women) and their parents. Dyadic correlations were constructed to determine the value similarity. In this study, the general value orientation and the family values were objects of research. We measured the subjective well-being with the Satisfaction with Life Scale and we used the Network of Relationships Inventory (NRI) to measure the relationship quality. Associations between subjective well-being and value similarity, and between subjective well-being and relationship quality, as well as mediation effects, were found. All effects depend on gender and perspective.
Keywords: Social Sciences (miscellaneous)

Intergenerational Value Similarity in Adulthood - Hoellger, Christian; Sommer, Sabrina; Albert, Isabelle; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on value similarity between parents and their children during adulthood. The interplay between gender, age, relationship quality, and frequency of contact on value similarity was analyzed. A total of 600 adult German children (53.8% women) and their parents took part in a questionnaire study. Value orientation was measured with a short version of Schwartz’s Portrait Values Questionnaire, and relationship quality with the Network of Relationships Inventory (Furman & Buhrmeister, 1992).Value similarity was higher in mother–daughter dyads compared to mother–son dyads, but in the other dyads, no significant differences were found. Regarding relationship quality, verbal intimacy was not related to value similarity. Parental satisfaction was associated with value similarity in the father–child dyads. Satisfaction, as perceived by adult children, was linked to value similarity in mother–child and father–son dyads. Furthermore, the frequency of contact related to value similarity between mothers and sons.
Keywords: Social Sciences (miscellaneous)

Legitimation Strategies as Valuable Signals in Nonfinancial Reporting? Effects on Investor Decision-Making - Hahn, Rüdiger; Reimsbach, Daniel; Kotzian, Peter; Feder, Madeleine; Weißenberger, Barbara E. (Business & Society)
Companies disclosing negative aspects in sustainability reports often employ legitimation strategies to present mishaps in a favorable light. In incentivized experiments, we find that nonprofessional investors divest from companies with a negative sustainability-related incident, and that symbolic legitimation (which only evasively explains a negative incident) is not a strong enough signal to counter this divestment behavior. Even substantial legitimation (which reports on measures and behavioral change) mitigates the divestment decisions only if the company reports on concrete remediation actions in morally charged situations, such as social or environmental incidents. We elaborate these results in light of signaling and screening theory, and suggest the conceptual extension of “costly signals” to what we call “valuable signals.” We argue that valuable signals need be not only costly for the sender from an economic perspective but also perceived as appropriate by the receiver from a noneconomic perspective.
Keywords: Social Sciences (miscellaneous); Business; Management and Accounting (miscellaneous)

The Personal Is Theoretical and the Past Is Present: Blurring the Lines in Contemporary Anti-Racist Writing - Hartmann, Alexandra (Open Cultural Studies)
Abstract This article studies the anti-racist writings by contemporary scholars Cornel West, Eddie S. Glaude, Jr., George Yancy, and Claudia Rankine. It uncovers how they include personal narratives in their works in order to theorise the workings of white hegemony in the twenty-first century. In doing so, I argue, they productively blur the lines between the personal and the theoretical as well as between the past and the present. Consequently, they problematise the notion of abstract theorising, the myth of continuous racial progress as well as conceptions of postracialism.
Keywords: General Social Sciences; General Arts and Humanities

Reflexive anthropomorphism: Ontological ignorance, or ignorant ontology? - Klowait, Nils (Sociological Journal)
Keywords: General Social Sciences

The Personal Is Theoretical and the Past Is Present: Blurring the Lines in Contemporary Anti-Racist Writing - Hartmann, Alexandra (Open Cultural Studies)
Abstract This article studies the anti-racist writings by contemporary scholars Cornel West, Eddie S. Glaude, Jr., George Yancy, and Claudia Rankine. It uncovers how they include personal narratives in their works in order to theorise the workings of white hegemony in the twenty-first century. In doing so, I argue, they productively blur the lines between the personal and the theoretical as well as between the past and the present. Consequently, they problematise the notion of abstract theorising, the myth of continuous racial progress as well as conceptions of postracialism.
Keywords: General Social Sciences; General Arts and Humanities

Effects of additional knowledge of results on modifying highly practiced acyclic swimming techniques with knowledge of performance - Krause, Daniel (International Journal of Sports Science & Coaching)
The author investigated the effects of additional knowledge of results on modifying swimming starts and turns with video-based knowledge of performance. A total of 18 swimming experts (15–18 years of age) learned modifications of start and turn techniques with knowledge of performance or a combination of knowledge of performance and knowledge of results. The feedback condition was switched between the groups from experiment 1 to experiment 2. Both experiments contained 50 trials with augmented feedback distributed over five sessions. Both experiments revealed no detrimental effects of additional knowledge of results on process-related performance variables. With respect to the result-related variables (start time and turn time), only the groups without knowledge of results exhibited temporary impairment in the immediate retention tests. The results are largely replicated in both experiments. Knowledge of results seems to have positive effects on modifying with knowledge of performance. The presence of knowledge of results might reduce the deautomatizing conscious control processes that are induced by knowledge of performance and might cause temporary performance impairments.
Keywords: Social Sciences (miscellaneous)

Tackling Complexity in Business and Society Research: The Methodological and Thematic Potential of Factorial Surveys - Oll, Josua; Hahn, Rüdiger; Reimsbach, Daniel; Kotzian, Peter (Business & Society)
Factorial surveys (FSs) integrate elements of survey research and classical experiments. Using a large number of respondents in a controlled setting, FSs approximate complex and realistic judgment situations through so-called vignettes—that is, carefully designed descriptions of hypothetical people, social situations, or scenarios. Despite being rooted, and predominantly applied, in sociology, FSs are particularly promising for business and society (B&S) scholars. Given the multiplicity, inherent complexity, and sometimes fuzziness of B&S research objects, conventional research methods inevitably reach their limits. This article, therefore, systematically presents methodological and thematic opportunities for FS studies in B&S research. It is argued that FSs are well suited to dealing with the complex interplay of societal-, organizational-, and individual-level factors in B&S research and to studying the principles underlying human perceptions, attitudes, values, social norms, and (anticipated) behavior. The application of the FS method is illustrated based on a showcase example in the realm of socially responsible investments (SRIs). As the literature on the conceptualization of FSs is limited, methodological challenges are addressed to guide B&S researchers past the common methodological pitfalls.
Keywords: Social Sciences (miscellaneous); Business; Management and Accounting (miscellaneous)

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

Rezension zu Alfred K. Treml „Warum der Berg ruft. Bergsteigen aus evolutionstheoretischer Sicht“ - Meier, Heiko (Sport und Gesellschaft)
Keywords: Philosophy; Social Sciences (miscellaneous); History